(NwOSPOMINANIQ(B. /s - (NmE]ERSKIJ(B, (NwLADIMIR pETROWI^s 1839-1914 ((NmOSKWA (B:s (NzAHAROW(B,s, 2003)
(NkNQZX w(B.(Np(B. (NmE]ERSKIJ (B- (NPUBLICIST(B, (NPROZAIK(B, (NWNUK nIKOLAQ kARAMZINA(B, (NDRUG aLEKSANDRA (BIII. (NpOSTOQNNO PODWERGAL PATRIOTI^ESKOJ KRITIKE GOSUDARSTWENNU@ B@ROKRATI@ I WYS[IJ SWET(B, (NODNOWREMENNO OB_QWIW WOJNU REWOL@CIONNOMU NIGILIZMU I LIBERALIZMU(B.s
(NnA OBOROTE TIT(B.(NL(B. (NI W WYP(B. (NDAN(B. (NZAGL(B.: (NmOI WOSPOMINANIQs
Keywords: (NmE]ERSKIJ(B, (NwLADIMIR pETROWI^s; (NrOSSIQs -- (NiSTORIQs -- 19 (NW(B.s; (NiSTORIQ (B- (NrOSSIQ (B- 19 (NW(B. - (NwOSPOMINANIQs